Lesions to Polar/Orbital Prefrontal Cortex Selectively Impair Reasoning about Emotional Material - Goel, Vinod (Neuropsychologia, 2017)
While it is widely accepted that lesions to orbital prefrontal cortex lead to emotion related disruptions and poor decision-making, there is very little patient data on this issue involving actual logical reasoning tasks. We tested patients with circumscribed, focal lesions largely confined to polar/orbital prefrontal cortex (BA 10 & 11) (N=17) on logical reasoning tasks involving neutral and emotional content, and compared their performance to that of an age and education-matched normal control group (N=22) and a posterior lesion control group (N=24). Our results revealed a significant group by content interaction driven by a selective impairment in the polar/orbital prefrontal cortex group compared to healthy normal controls and to the parietal patient group, in the emotional content reasoning trials. Subsequent analyses of congruent and incongruent reasoning trials indicated that this impairment was driven by the poor performance of patients with polar/orbital lesions in the incongruent trials. We conclude that the polar/orbital prefrontal cortex plays a critical role in filtering emotionally charged content from the material before it is passed on to the reasoning system in lateral/dorsal regions of prefrontal cortex. Where unfiltered content is passed to the reasoning engine, either as a result of pathology (as in the case of our patients) or as a result of individual differences, reasoning performance suffers.